Harnessing the immune system in the battle against breast cancer - Elizabeth S Nakasone; Sara A Hurvitz; Kelly E McCann (Drugs in Context, 2018)
Breast cancer is the most prevalent malignancy in women and the second most common cause of cancer-related death worldwide. Despite major innovations in early detection and advanced therapeutics, up to 30% of women with nodenegative breast cancer and 70% of women with node-positive breast cancer will develop recurrence. The recognition that breast tumors are infiltrated by a complex array of immune cells that influence their development, progression, and metastasis, as well as their responsiveness to systemic therapies has sparked major interest in the development of immunotherapies. In fact, not only the native host immune system can be altered to promote potent antitumor response, but also its components can be manipulated to generate effective therapeutic strategies. We present here a review of the major approaches to immunotherapy in breast cancers, both successes and failures, as well as new therapies on the horizon.